Implementasi Manajemen Sarana dan Prasarana Berbasis Maslahah di Institut Agama Islam Sahid (INAIS) - Hafid Fadilah (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2023)
Infrastructure is an important factor in improving the quality of education, the Sahid Islamic Institute in the last two years has been very concerned about the fulfillment of facilities and infrastructure, this study aims to: 1) Describe the implementation of management of facilities and infrastructure in improving the quality of education at the Sahid Islamic Religious Institute, 2) Analyze the constraints and solutions in the implementation of management of facilities and infrastructure in increasing educational benefits at the Sahid Islamic Institute of Religion. This study uses a qualitative method. The research was conducted at the Sahid Islamic Institute, from August to November 2019. The subjects in this study were the Head of General Affairs and Finance and the Facilities and Infrastructure Section of the Sahid Islamic Institute. The informants in the research are lecturers and students. Data collection techniques by means of interviews, observation and documentation. The data validation technique uses data tranqulation and source triangulation. Data analysis techniques using interactive methods, data collection, data presentation, data reduction and drawing conclusions. The results of the study revealed that (1) the implementation of management of facilities and infrastructure in improving the quality of education at the Sahid Islamic Institute was carried out by means and infrastructure planning (Planing), namely Campus coordination meetings, determining Campus programs, and determining the needs of educational facilities and infrastructure.